Evaluation of Water Resources Utilization Efficiency in Guangdong Province Based on the DEA–Malmquist Model - Cheng, Lifen; Song, Song; Xie, Yufeng (Frontiers in Environmental Science, 2022)
In this study, we examined the temporal and spatial trends of water utilization efficiency in the highly developed Guangdong Province based on a data envelopment analysis (DEA) model and Malmquist index, trying to evaluate and predict the water utilization status in prefecture-level cities from the input–output perspective. The results showed that the water utilization efficiency in Guangdong Province in 2012–2018 was on a fluctuating upward trend, although the utilization efficiency had not reached the DEA efficiency; spatially, the water utilization efficiency in Guangdong Province was relatively high in the Pearl River Delta and the surrounding cities, but low in the Western Guangdong region; in the perspective of efficiency decomposition factors, technological change was the most pervasive driving force of the water utilization efficiency. Pearl River Delta and Northern Guangdong made progress in productivity due to the advantages of scale expansion benefit. Eastern Guangdong achieved improvement in all-over parameters and made the largest growth in water utilization efficiency, while Western Guangdong basically profited from organizational management during the study period; the prediction analysis revealed a continuous increase in the water utilization efficiency in Guangdong Province during 2019–2025 with an average annual growth rate of about 0.6%, benefiting mainly from the technological innovation and secondly from management renewal, while scale expansion benefit tended to decline. Furthermore, spatial heterogeneity exhibited a decreasing tendency in the future owing to the rapid water utilization efficiency increase in the Western and Eastern Guangdong. It is suggested that the technological innovation and the integrated management capability in water use should be paid more attention to enhance the water utilization efficiency in Guangdong Province. Achieving a balance between economic growth and water resource protection, and promoting the sustainable development of the nature-economy-society compound system is of the utmost priority in Guangdong.